2009
DOI: 10.1177/0734242x09345275
|View full text |Cite
|
Sign up to set email alerts
|

Composting and compost utilization: accounting of greenhouse gases and global warming contributions

Abstract: Greenhouse gas (GHG) emissions related to composting of organic waste and use of compost was assessed from a waste management perspective. The GHG accounting for composting includes use of electricity and fuels, emissions of methane and nitrous oxide from the composting process, and savings obtained by the use of the compost. The GHG account depends on waste type and composition (kitchen organics, garden waste), technology type (open systems, closed systems, home composting), the efficiency of off-gas cleaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
215
2
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(237 citation statements)
references
References 32 publications
11
215
2
9
Order By: Relevance
“…This is the case of the AD plant, which is beneficial in terms of energy production, but it will be penalized by the refuse transport to a landfill and its decomposition due to greenhouse gas emissions. Also, compost utilization has a beneficial effect 46 on those plants with the higher productivity per mass of OFMSW. However, in this work, LCA is only used to demonstrate that a new functional unit should be used in the assessment of the environmental impact of the biological treatment of source-separated P r e -p r i n t…”
Section: P R E -P R I N Tmentioning
confidence: 99%
“…This is the case of the AD plant, which is beneficial in terms of energy production, but it will be penalized by the refuse transport to a landfill and its decomposition due to greenhouse gas emissions. Also, compost utilization has a beneficial effect 46 on those plants with the higher productivity per mass of OFMSW. However, in this work, LCA is only used to demonstrate that a new functional unit should be used in the assessment of the environmental impact of the biological treatment of source-separated P r e -p r i n t…”
Section: P R E -P R I N Tmentioning
confidence: 99%
“…The refinery process comprised two reactors: in the first reactor waste was heated by injection of hot water to about 75 °C for approximately 0.5-1 hours, then cooled to about [50][51][52][53][54][55] °C before entering the second reactor where enzymes were added (about 5 kg t -1 MSW) resulting in hydrolysis and break-down of bonds in the organic materials, thereby suspending organic materials in the liquid phase (44). The retention time was about 10-16 hour.…”
Section: Lci Of Waste Technologiesmentioning
confidence: 99%
“…The remaining part is stable organic matter that have been reported to have the potential of binding C with soil when applied on land for 100-1000 years resulting in considerable reductions of CO2 emissions to the atmosphere (Boldrin et al, 2009;Favoino and Hogg 2008). Therefore, it can be concluded that ANC con- …”
Section: Nitrogen Mineralizationmentioning
confidence: 99%
“…For such waste, optimized biological processes or means for waste reduction, reuse and recovery would be preferable. These processes convert the green waste or food leftover in to organic fertilizers such as compost (Favoino and Hogg, 2008;Hargreaves et al, 2008b;Boldrin et al, 2009Kumar, 2011) that may fulfill the increasing demand of chemical fertilizers for crop production in Pakistan, which is about 13% annually (Pakistan Bureau of Statistics, 2016).…”
Section: Introductionmentioning
confidence: 99%